2015
DOI: 10.1111/1365-2435.12418
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of water and nitrogen relationships between mistletoes and their hosts: broad‐scale tests of old and enduring hypotheses

Abstract: Summary 1.Mistletoes use far more water per unit carbon fixed during photosynthesis than their hosts (i.e. they have lower 'water use efficiency', WUE). The widely cited 'nitrogen-parasitism hypothesis' posits that N is the most limiting resource for mistletoes and that they use their faster transpiration rates to acquire sufficient N from the host xylem. In a rather different context, the 'mimicry hypothesis' arose in the literature suggesting that some mistletoes mimic the morphology of host leaves in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 86 publications
(176 reference statements)
7
57
0
Order By: Relevance
“…A1). The correspondence between host and mistletoe leaf N concentration was already reported in a global analysis considering more than 160 mistletoe–host pairs (Scalon and Wright ), but the fact that leaf P concentration of mistletoes does not reflect that of their hosts suggests that the maintenance of higher P concentration may be achieved through the resorption process.…”
Section: Discussionmentioning
confidence: 58%
“…A1). The correspondence between host and mistletoe leaf N concentration was already reported in a global analysis considering more than 160 mistletoe–host pairs (Scalon and Wright ), but the fact that leaf P concentration of mistletoes does not reflect that of their hosts suggests that the maintenance of higher P concentration may be achieved through the resorption process.…”
Section: Discussionmentioning
confidence: 58%
“…The authors suggested that this correspondence could occur because of similar responses to external factors, such as the water VPD (Ullmann et al 1985). In a global analysis, Scalon and Wright (2015) showed that mistletoes become more conservative in their water use with increasing aridity, suggesting that they respond to environmental constraints in a manner similar to that of their hosts. Alternatively, mistletoes could be responding to an internal mechanism driven by the host, such as hormonal control, as suggested by Ullmann et al (1985).…”
Section: Stomatal Behaviour and Morphologymentioning
confidence: 99%
“…The changes caused by mistletoe parasitism in pine (Zweifel et al. , Scalon and Wright ) transform pine tissues into a worse food for the insect due to stronger induced defenses (Lázaro‐González et al. ) and a reduction of mineral nutrients (Mutlu et al.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the indirect effects of mistletoe on arthropod herbivores as a TMII, via changes in the quality (trait) of the pine as food. The changes caused by mistletoe parasitism in pine (Zweifel et al 2012, Scalon andWright 2015) transform pine tissues into a worse food for the insect due to stronger induced defenses (L azaro-Gonz alez et al 2019) and a reduction of mineral nutrients (Mutlu et al 2016). These negative effects of mistletoe on pines prove especially stressful at a site such as Sierra de Baza, with poor soils ) and a severe summer drought, where high mistletoe load inevitably leads to the death of the pine .…”
Section: Discussionmentioning
confidence: 99%